In vitro aflatoxin B1 binding capacity by two Enterococcus faecium strains isolated from healthy dog faeces - Fernandez Juri, Maria Guillermina (2015)
Aim: This study evaluated the binding capacity of aflatoxin B1 (AFB1) by two Enterococcus faecium strains (MF4 and GJ40) isolated from faeces from healthy dogs. Materials and Methods: The binding assay was performed using 50 and 100 ppb of AFB1 analysing the effects of the viability, incubation time and pH on AFB1 binding. Binding stability was determined by washing three times the bacteria-AFB1 complexes with phosphate buffer saline. Results: Both GJ40 and MF4 strains have the ability to remove AFB1 from aqueous solution. Viable cells were slightly more effective in AFB1 binding than nonviable ones for both strains. Enterococcus faeciumGJ40 removes 24–27% and 17–24%, and Ent. faeciumMF4 removes 36–42% and 27–32% of AFB1 (50 and 100 ppb, respectively) throughout a 48 h incubation period. In general, the removal of AFB1 was highest at pH 7·00 for both strains. The stability of the bacteria-AFB1 complex formed was found to be high (up to 50% of AFB1 remained bounded in bacterial cell after three washes with phosphate buffered saline). Conclusion: The Ent. faecium strains assayed are capable of removing AFB1 under different conditions in vitro. Significance and Impact of the Study: This is the first AFB1 binding assay performed with Ent. faecium strains isolated from dog faeces, being an interesting strategy for AFB1 decontamination of pet food.